Prevalence of Hepatitis B and Its Associated Factors Among Pregnant Women in Mogadishu, Somalia - Dahie, Hassan Abdullahi; Heyle, Abdullahi Ali (Archives of Business Research, 2017)
Background: Hepatitis B is a major global health problem caused by viral infection that attacks the liver and can cause both acute and chronic disease. There are about 65 million individuals who carry HBV in Africa, with a 25% mortality risk. In sub-Saharan Africa, the prevalence of HBV infection ranges from 9-20%. Pregnant mothers who test positive for both hepatitis B surface antigen (HBsAg) and hepatitis B e antigen (HBeAg) have 70–90% risk of transmitting infection to their newborn infants and about 10–40% risk if they test positive for only HBsAg. Therefore, pregnant women should be routinely screened for HBsAg and hepatitis B vaccine administered at birth to the infants whose mothers test positive. Objective: To identify prevalence of Hepatitis B (HBsAg) and its associated factors among pregnant women in Mogadishu, Somalia. Methodology: This was a hospital based cross-sectional study. This design was used to identify potential risk factors associated with development of Hepatitis B virus. Cross-sectional was used to assess the frequency and distribution of Hepatitis B among pregnant women and to investigate factors associated with it. The study instruments were structured questionnaires which were both categorical and open ended. Data was entered and analyzed with SPSS version 16.0. Both Univariate and Bivariate analysis were carried out to see frequencies and significant associations, a P-value less than 0.05 was considered as significant association. Result: The mean age of the respondents was 24.65 (±6.05) years. It was found that women in the age category of (³30) were more likely to get Hepatitis B compared to those below categories (OR 1.69, 95%CI 1.11-1.89). The study revealed that 96.4% of the respondents were unemployed whose majority (79.1%) were from families of low economic status and these were 2.1 times more likely to contract Hepatitis B compared to the pregnant women who are in the category of middle and high economic status (OR 2.1 95% CI 1.25-3.21). The study reported that mothers with gravidity of 7 and more were 2.1 times (OR 2.1, 95%CI 1.31-3.04) more likely to get hepatitis B compared to mothers with gravidity between1-6. Moreover, prevalence of hospital delivery was around one-third (36.5%) while almost another one-third was attended by TBAs. Finally, the study has found that the seroprevalence of HBsAg among pregnant women was 4.12%. Conclusion and Recommendation: The study found out that HBsAg prevalence among pregnant women in Mogadishu was 4.12%, significantly associated with age, economic status, gravidity, birth attendant and abortion. It is recommended that MoH and health professionals adopt universal screening of all pregnant women for HBsAg during each pregnancy, prophylaxis and routine vaccination of both mothers and infants and also management of Hepatitis B cases.